THE DEPENDENCE OF THE STRUCTURAL CHANGES ALONG THE RUNNING SURFACE OF RAIL WHEELS ON THE TYPE OF BRAKE SYSTEM - Vakulenko, I. O. (Science and Transport Progress, 2008)
The destruction occurrence in a railroad wheel is caused by formation of the high local stresses produced by the inhomogeneous plastic deformation, the cyclic temperature change during and after braking as well as the type of brake system.